INOVASI LITERASI: PLANG EDUKASI BERBASIS INFORMASI LINGKUNGAN UNTUK MENDORONG PERILAKU RAMAH LINGKUNGAN DI SMA N 1 NAMORAMBE - Martua Reynhat Sitanggang Gusar; Juliaster Marbun; Ido parningotan Sitinjak; Winda Simbolon (Merwinspy Publisher, 2026)
The Community Service Program (PkM) highlighted the limited understanding of the impact of daily habits—such as improper waste disposal—underscoring the need for educational media that is simple, appealing, and easily accessible. This program aimed to: (1) improve environmental literacy through visual educational media, (2) encourage environmentally friendly behavior among students and school members, and (3) develop educational signboards as an innovative model of environmental learning media.The implementation included site surveys, administrative preparation, media production, socialization activities, communal clean-up, installation of educational signboards, and final report preparation. The results showed that the signboards effectively increased students’ understanding of the harmful effects of non-degradable waste and the importance of proper environmental management. Supporting activities such as the Learning House (RuBel), communal work, and administrative assistance also contributed positively to the school environment. Overall, the program successfully achieved its objectives and provided a tangible contribution to improving environmental literacy and eco-friendly behavior. It is hoped that this PkM initiative can be sustained and serve as a model for environmental education in other schools.